GRP-045 Contradictions in the Interpretation of Drug/Supplement Interactions and Difficulties of Their Management in Everyday Clinical Practise. (12th March 2013) - Végh, A; Vida, RG; Nyaka, B; Botz, L
Abstract : Background: The growing use of supplementary products (herbal remedies, food supplements, etc.) poses an unignorable and poorly explored risk to hospital patients. The results of our previous study [1] show that 85.5% of hospital patients took at least one supplementary product; and with one patient out of four we have identified potential interactions. However, several questions arise about their clinical relevance: (1) Might the interaction harm the patient? (2) Is treatment modification or close monitoring necessary? (3) Is it reasonable to prohibit the use of any supplement? Purpose: To explore and study those determinants that need to be taken into account when managing drug/supplement interactions. Materials and Methods: Taking the results of our previous study as a basis we have systematically evaluated the literature and the available authentic databases. Results: There are significant differences between the databases we have looked at, as to which interactions are present in the system, and how broad a spectrum of active ingredients is included when a known case of interaction occurs. We identified the following factors, which have to be taken into account when evaluating a potential interaction: type of underlying evidence (in vitro studies, case reports, clinical trials, etc.) which form of a given interacting substance has been reported on (species, plant-part, type of extract, etc.) and whether this component is present in the product mechanism and dose dependence of the interaction which patient groups are more likely to develop symptoms due to the interaction We evaluated 155 components found in supplementary products by the listed criteria, then assessed the relevance and classification of interactions. Conclusions: Special software, that contains all the recommended criteria we have set up, could become an effective tool for preventive screening of interactions on hospital admission. Reference: A. Végh, E. Lankó, A. Fittler, L. Botz (2012): Identification and prevention of deleterious effects of supplementary health products on medical therapy – A challenge for clinical pharmacists; abstract in EJHP 19 (2), p. 95. No conflict of interest.